White matter microstructure in ultra-high risk and first episode schizophrenia: A prospective study. (30th January 2016) - Rigucci, Silvia; Santi, Giulia; Corigliano, Valentina; Imola, Annamaria; Rossi-Espagnet, Camilla; Mancinelli, Iginia; De Pisa, Eleonora; Manfredi, Giovanni; Bozzao, Alessandro; Carducci, Filippo; Girardi, Paolo; Comparelli, Anna
Abstract: There is increasing evidence of white matter (WM) pathology in schizophrenia, but its role at the very early stage of the disorder remains unclear. In an exploration of WM microstructure in ultra-high risk (UHR) subjects and first episode schizophrenia (FES), 34 FES, 27 UHR and 26 healthy control (HC) subjects underwent a magnetic resonance imaging (MRI) tract based spatial statistics (TBSS) investigation. Whole brain fractional anisotropy (FA), mean diffusivity (MD), radial (RD) and axial diffusivity (AD) values were extracted. UHR subjects who later developed psychosis showed lower FA compared with HC in the corpus callosum (CC), the left superior and inferior longitudinal fasciculus, the left inferior fronto-occipital fasciculs (IFO), and the forceps; RD was significantly higher in the CC, the forceps, the anterior thalamic radiation bilaterally, and the cingulum bundle. FES, compared to HC, showed a significant FA reduction of the CC, the superior and inferior longitudinal fasciculi bilaterally, the IFO bilaterally, the corona radiate bilaterally, and the forceps; while RD was found to be significantly increased in the left superior longitudinal fasciculus. UHR who later developed psychosis had WM abnormalities affecting brain pathways that are crucial for intra- and inter-hemispheric connections. Highlights: FES and UHR who developed-psychosis have similar WM abnormalities. UHR who-did-not-developed-psychosis and controls are indistinguishable in terms of WM integrity. WM abnormalities in UHR affect brain connections commonly disrupted in schizophrenia.